Effect of Surfactant on Spectrofluorimetric Determination of Fe(III) - Tavallali, Hossein; Nejabat, Rozita (Asian Journal of Chemistry, 2010)
In present studies, a simple and efficient spectrofluorimetric method has been described for trace determination of Fe(III). Method is based on quenching effect of traces of Fe3+ on fluorescence intensity of Ce3+ in the presence of TX-100 as a surfactant. The signal for Ce-Fe-TX-100 is monitored at lex= 303.5 nm and lem = 354 nm. Optimum conditions were pH = 4, [TX-100] = 8.33 × 10-5 % v/v and 25 ºC, which allows the determination of 0.2-15 μg/mL of Fe3+ with limit of detection of 0.13 μg/mL. The quenching effects of some inorganic anions and cations were studied and showed there isn't serious interferance. This system was chosen to develop a rapid and simple method for its determination of Fe3+ in pharmaceutical formulation.